2013
DOI: 10.1038/ncb2722
|View full text |Cite
|
Sign up to set email alerts
|

Cullin' PLK1 from kinetochores

Abstract: To ensure proper attachment of all chromosomes to the spindle, PLK1 has to associate with kinetochores during prometaphase and must be released from these sites before sister chromatid separation can begin. The monoubiquitylation of PLK1 by the ubiquitin ligase CUL3-KLHL22 is now identified as a critical step in promoting the release of PLK1 from kinetochores, pushing non-proteolytic ubiquitylation into the limelight of cell division research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…For details see the main text. leads to accumulation of PLK1 at kinetochores, chromosome alignment defects, SAC potentiation and mitotic arrest resulting in apoptotic death [39,42,43]. It would be interesting to understand if kinetochore removal of K492-ubiquitylated PLK1 is helped by an action of a downstream ubiquitin receptor analogous to UBASH3B.…”
Section: Fig 2 Non-proteolytic Cul3 Pathways During Cell Divisionmentioning
confidence: 99%
“…For details see the main text. leads to accumulation of PLK1 at kinetochores, chromosome alignment defects, SAC potentiation and mitotic arrest resulting in apoptotic death [39,42,43]. It would be interesting to understand if kinetochore removal of K492-ubiquitylated PLK1 is helped by an action of a downstream ubiquitin receptor analogous to UBASH3B.…”
Section: Fig 2 Non-proteolytic Cul3 Pathways During Cell Divisionmentioning
confidence: 99%
“…It plays an important role in centriole maturation [11][12][13], Golgi disintegration [14], spindle assembling and function [15,16], kinetochore function [17,18], centromere assembling [19] and cytokinesis [20]. It also facilitates DNA replication [21], mitotic entry [22], separation of sister chromatid [23], chromosome condensation [24] and APC/C activity [25]. It has been reported that PLK1 is frequently over-expressed in numerous cancers (such as esophageal cancer, colon cancer, breast cancer, non-small cell lung cancer, endometrial cancer, etc.…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] Experiments with antiPrc1 microinjection demonstrated that cell division is blocked, without any influence on the nuclear separation; this suggests that Prc1 would be essential for cytokinetic achievement. [21] Plk1, on the other hand, participates at several stages of the cell cycle, and is an essential protein in cytokinesis.…”
mentioning
confidence: 97%
“…To begin, Prc1 is inhibited during mitosis onset through Cdk1 phosphorylation in two action sites-T470 and T481and, indeed, mutation at such sites causes premature recruitment of Plk1 and Prc1, resulting in prometaphase arrest and blocking the progression of mitosis. [19,20] Experiments with anti-Prc1 microinjection demonstrated that cell division is blocked, without any influence on the nuclear separation; this suggests that Prc1 would be essential for cytokinetic achievement. [21] Plk1, on the other hand, participates at several stages of the cell cycle, and is an essential protein in cytokinesis.…”
mentioning
confidence: 99%
See 1 more Smart Citation